The content of copper and zinc in the natural environment components of the park areas - Morgacheva Natalya V.; Dubrovina Olga A.; Shcherbatykh Sergey V.; Sotnikova Elena B. (E3S Web of Conferences, 2023)
The influence of man-made pollution on the accumulation of copper and zinc in the soil and plants of the forest park zones of Yelets was studied on the example of the woody–plant natural environment components prevailing in them hanging birch (Betula pendula Roth) and creeping wheatgrass (Elytrigia repens). As a result of the conducted studies, the features of the deposition of copper and zinc in the plant organs were revealed, and the total accumulation of the studied elements in the soil under green plantations was estimated.